CONTRIBUTION OFAGRONOMIC TRAITS TO THE YIELD OF Coffea canephora PIERRE EX A. FROEHNER HULLED COFFEE - Spinelli, Victor Mouzinho; Moraes, Marcos Santana; Barbosa Alves, Darlan Sanches; Rocha, Rodrigo Barros; Ramalho, André Rostand; Teixeira, Alexsandro Lara (Coffee Science - ISSN 1984-3909, 2018)
The evaluation of morphological characters related to the hulled coffee yield subsidizes the selection of Coffea canephora plants that combine a set of favorable traits. The aim of this study was to evaluate the direct and indirect effects of agronomic traits on the production of hulled coffee to subside the plant selection. To this, nine morphological descriptors were evaluated of 130 clones of the botanical varieties Conilon and Robusta over two crop years in the experimental field of Embrapa, in the municipality of Ouro Preto do Oeste, state of Rondônia (RO). To quantify the genetic variability the path analysis and the Scott Knott cluster test were used. The effect of genotype x year interaction was significant for eight of the nine characteristics analyzed. The genotypes were clustered in three to five classes, subsidizing the establishment of a scale to evaluate the variability of this genetic resource. Pathway analysis indicated that the number of plagiotropic branches and the number of rosettes per productive branch were the traits that exhibited the greatest direct effect on hulled coffee yield. These results show that it is possible to select plants with complementarity traits which favor a higher production of hulled coffee.